Photoluminescence and I -V Characteristics of Blended Conjugated Polymers/ZnO Nanoparticles - Cuong, Nguyen Kien; Khanh, Nguyen Quoc (VNU Journal of Science: Mathematics - Physics, 2016)
Abstract: The investigation of photoluminescence and current-voltage (I-V) characteristics of the MEH-PPV/PVK blended polymers doped with ZnO nanoparticles (ZnO NPs). First, PVK polymers were mixed with MEH-PPV in respect to the mass-ratio of 100:15, respectively. And then the MEH-PPV/PVK composites were doped with ZnO NPs with the mass-ratio of 10 wt%, 15 wt% and 20 wt% of total weight blended polymers.  Polymer light-emitting diodes (PLEDs), based on a hybrid composite, having structure of ITO/ MEH-PPV/PVK/ZnO/Al were made by spin-coated, and subsequently vacuum-thermally evaporated. UV-Vis absorption, photoluminescence properties, SEM micrographs of the hybrid composite layer as well as I -V characteristics of the PLED based on the MEH-PPV/ZnO-and PVK/ZnO-heterojunction were investigated. Results obtained show that the turn-on voltage of the polymers/ZnO-based PLED is lower than that of the polymers-based PLED without doped ZnO NPs. This is due to the Auger-assisted energy up-conversion process occurring at the polymers/ZnO-heterojunction that could enhance the luminescence efficiency of the PLED. Keywords: PLED, photoluminescence efficiency, MEH-PPV, PVK, SEM, spin coating, thermal vacuum evaporation